New records of parasite nematodes from wildlife animals in Peru - Tantaleán, Manuel (1998)
In this paper, Dipetalonema graciliformis Freitas, 1964 parasite of Saguinus labiatus; Evaginuris branickii (McClure, 1932) Quentin, 1973 of Dinomys branickii, Alaeuris caudatus (Lent & Freitas, 1948) of Iguana iguana and Serpinema amazonicus of Podocnemis expansa are recorded for the first time. Also, Saguinus labiatus is considered as new host for Dipetalonema graciliformis.